A Survey on Bandwidth Management in MANET - Jagadev, Nibedita; Kumar Pattanayak, Binod; Singh, Debabrata; Sahoo, Sipra (International Journal of Engineering and Technology, 2018)
Mobile ad-hoc network (MANET) are self-configuring without any fixed infrastructure. In MANET the challenge of providing QoS support during multimedia application is an open problem.Â To enhance the network throughput adequate amount of bandwidth is required. Bandwidth management in MANET plays a vital role in improving the networks overall performance. In this paper a systematic study has been carried out about challenging issues associated with bandwidth management during routing in MANET and analysis has been done about different models of bandwidth management.Â